MATLAB/Simulink Based Instantaneous Solar Radiation Modeling, Validation and Performance Analysis of Fixed and Tracking Surfaces for the Climatic Conditions of Lahore City, Pakistan - Naseer Ahmad (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Mathematical modeling, simulation and experimental validation of instantaneous solar radiation is conducted in this article. The input parameters of the developed model are solar constant, latitude & longitude of the selected site, collector surface azimuth and elevation angle. The whole model is developed in MATLAB/Simulink and plots global radiation for any selected day of the year. To validate the model, actual data from RETScreen (energy management software) is taken and compared with the predicted data from developed model. During the whole year the predicted specific insolation is 226.65 MJ/m2/day and actual is 202.14 MJ/m2/day. The percentage error of the predicted data is 10.8% higher than the actual data. The validated model is used to calculate the monthly received solar radiation energy for the fixed surface and tracking surface. The yearly harvested solar energy by horizontal, yearly and monthly optimal tilt surfaces are 6828 MJ/m2, 7405 MJ/m2 and 7761 MJ/m2 respectively. Yearly insolation gain of the yearly optimal tilt and monthly optimal tilt collector surface is 8% and 14% as compared to the energy harvested by horizontal surface. For the single and dual axis tracking surfaces, yearly harvested energy is 8843 MJ/m2 and 9374 MJ/m2 respectively and this figure is 30% and 37% more as compared to the horizontal surface. If the insolation received by yearly optimal tilt is considered as reference value, then energy gain for monthly tilt, single and dual axis tracking is recorded as 5%, 19% and 27% respectively